The prevalence of Staphylococcus saprophyticus in patient of Urinary Tract Infection (UTI) in Falluja City - Hassan A. Muttar; Hassan A. Abd Alreda; Hamdi Al-Janabi; Idham A Assafi (مجلة جامعة الانبار للعلوم الصرفة, 2012)
This study was conducted to evaluate the incidence of Staphylococcus saprophyticus and its role in urinary tract infection in male and female For achieving this goal, 400 midstream urine samples were collected from patients suffering from UTI in Al-Falluja hospital (male and female) for the period between 114 to30102006, samples were cultured on mannitol salt agar and Staph. 110 and different biochemical tests and API Staph. Were used to ensuring the diagnosis disc diffusion method was used to test the susceptibility of these isolates to different antibiotics (11 antibiotics) which used as therapeutics. The results could be summarized as follows: 1:-Isolation and identification of 16 isolates belonging to Staphylococcus saprophyticus comprising 4% out of the total number of infection cases with the dominance of female infection. 2:-The rate of infection increase in compared with city. 3:-All Staphylococcus saprophyticus isolates were sensitive (87.5%) to Ceftazidime, 75% Refampicin, while these isolates were resistance to Lincomycin (100%), (81 %) Erthromycin ( 75%) Trimethoprim and the current study showed those plasmids are the genetic material that encoded the resistance to antibiotics.